Design of an IOT Based Online Monitoring Digital Stethoscope - B. Revanth Reddy; S. Roji Marjorie; P. Ramakrishna (Institute of Advanced Engineering and Science, 2018)
Acoustic stethoscopes have low sound levels. Digital stethoscope overcomes this issue by amplifying body sounds electronically. As the sound signals are transmitted electronically, it can be wireless and can provide noise reduction. Acoustic stethoscope can be changed into a digital stethoscope by inserting an electric capacity microphone onto its head. Heart sounds received from the microphone are processed, sampled and sound signals are converted analog to digital and sent wirelessly using the Internet of Things(IOT) techniques, so that multiple doctors can do auscultation and monitor conditions of the patient.